OPTIMALISASI PERAN PENDIDIK PAUD DALAM PROGRAM PERCEPATAN PENURUNAN STUNTING DI KOTA SURABAYA - Kusumawati, Mei Ariani; Hasibuan, Rachma (STKIP PGRI Situbondo, 2025)
This research is motivated by the urgency of the generation of healthy children in facing the digital era. The purpose of this study was to describe the role of PAUD educators in the acceleration program for stunting reduction in Surabaya City. This research uses library research method by collecting several sources of literature obtained from national and international journals, books, and some relevant research results. After the library data has been collected, the authors arrange and sort the data into new findings or new sources of information. The results of this study show that the role of PAUD educators has a very strategic and important role in (1) Counseling on the importance of the first 1000 days of life (HPK) for children from the womb to birth, even in the growth and development period; (2) Counseling on the dangers of stunting and how to prevent it to pregnant women, breastfeeding mothers and parents who have early childhood; (3) Providing facilities for families who have been affected by stunting to improve nutrition and nutrition so that there is a change in lifestyle in providing balanced nutrition. The recommended activities are also to maximize the delivery of training materials through the use of digital media